2010
DOI: 10.1002/jnr.22435
|View full text |Cite
|
Sign up to set email alerts
|

Glial cell line‐derived neurotrophic factor–secreting genetically modified human bone marrow‐derived mesenchymal stem cells promote recovery in a rat model of Parkinson's disease

Abstract: Parkinson's disease (PD) is a neurodegenerative disease characterized by progressive degeneration of nigrostriatal dopaminergic (DA) neurons. The therapeutic potential of glial cell line-derived neurotrophic factor (GDNF), the most potent neurotrophic factor for DA neurons, has been demonstrated in many experimental models of PD. However, chronic delivery of GDNF to DA neurons in the brain remains an unmet challenge. Here, we report the effects of GDNF-releasing Notch-induced human bone marrow-derived mesenchy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 104 publications
(137 reference statements)
0
47
0
Order By: Relevance
“…It was previously reported that naïve, neurotrophic factorsecreting, or neurally induced MSCs have therapeutic effects when transplanted into 6-OHDA-or MPTP-induced Parkinsonian animals (Biju et al, 2013;Capitelli et al, 2014;Dezawa et al, 2004;Glavaski-Joksimovic et al, 2010;McCoy et al, 2008;Park et al, 2014;Sadan et al, 2009;Wang et al, 2013;Weiss et al, 2006;Yan et al, 2013). A beneficial effect of the striatal transplantation of both SHEDs and DAergic neuronlike SHEDs was also previously reported (Wang et al, 2010).…”
Section: Discussionmentioning
confidence: 64%
“…It was previously reported that naïve, neurotrophic factorsecreting, or neurally induced MSCs have therapeutic effects when transplanted into 6-OHDA-or MPTP-induced Parkinsonian animals (Biju et al, 2013;Capitelli et al, 2014;Dezawa et al, 2004;Glavaski-Joksimovic et al, 2010;McCoy et al, 2008;Park et al, 2014;Sadan et al, 2009;Wang et al, 2013;Weiss et al, 2006;Yan et al, 2013). A beneficial effect of the striatal transplantation of both SHEDs and DAergic neuronlike SHEDs was also previously reported (Wang et al, 2010).…”
Section: Discussionmentioning
confidence: 64%
“…Studies carried out with PD rat models show some examples of the substantial, beneficial behavioural results after engineered BM-MSC administration with either GDNF [216,217] or persephin [218], which is another neurotrophic factor that promotes survival, proliferation, and differentiation of neurons [219]. demyelination and neuronal loss [220].…”
Section: Mscs In Neural Differentiation and Repairmentioning
confidence: 98%
“…ecSOD [158] GLP-1 [160] HCN1 [19] HCN4 [186,187] Fn14 [189] Wnt11 [164] HO-1 [167,168] My GA NEURAL DIFFERENTIATION AND REPAIR BDNF [22] [201] [203,204] GDNF [20] [207] [216,217] NGF [236] NT-3 [225,226] MNTS-1 [230] Shh [232] VEGF [21] GLP-1 [215] VIP [221] IL-10 [222] interferon-β [223] CXCR4 [205] TrkC [228] Ng Ng RA Nu Ma KIDNEY REPAIR HGF [23] GSTM1 [267] Survivin [268] …”
Section: Cartilage Productionmentioning
confidence: 99%
“…In rodent models of PD, continuous levodopa delivery by transferring genes for TH and GCH1 via an rAAV vector to striatal neurons has prevented dyskinesia and reversed both dyskinesia and sensorimotor behavioral deficits [81,82]. GDNF continues to be investigated via several different gene delivery techniques, including lentiviral vector and stem cells transduced ex vivo with the GDNF gene [83,84].…”
Section: Other Approachesmentioning
confidence: 98%